A Cone Beam Computed Tomography Study Among Dental Residents Based on a Questionnaire - Stoica, Alexandra Mihaela; Monea, Monica; Sita, Dragos Dan; Buruian, Mircea (European Scientific Journal, ESJ, 2016)
Objectives: The aim of our study was to analyse the utility of the CBCT systems among the dental residents form the Dental University of TarguMures. Material and methods: We conducted an anonymous survey using a questionnaire that included 11 questions. All the 55 participants from all dental specialties studied at the Dental University Center Targu-Mures. The completed questionnaires were collected the results were evaluated and statistically analyzed using chi-square test. Results: Most residents have learnt about the CBCT during the university studied by participating at different radio-imagistic courses outside the curriculum. Only 33 (60%) residents recommend daily a CBCT for supporting their diagnosis most of them being oral surgeons and 7 (12.72%) of them occasionally recommend between 1 and 5 CBCTs a month. Conclusions: The CBCT system used as an imagistic evaluation in all dental specialties is essential and the advantages can be found in the accuracy of establishing a correct diagnosis, creating a treatment plan and results evaluation.